PROPOSED BRAND ACTIVATION STRATEGY FOR A NEW WOMEN’S FASHION BUSINESS CASE STUDY: AUBRE AND LIESSE (The Indonesian Journal of Business Administration, 2019)
Since 2010 many local fashion brands have been established in Indonesia. The great demand and opportunity of fashion products and businesses create a high-level competition. In 2016 there were 1,230,988 fashion companies (BEKRAF, 2017) and the main competition is not with the foreign brands but with fellow local brands. As a new fashion brand, Aubre and Liesse has to formulate a brand activation strategy to enter the market, make the potential target market become aware with the brand and interested with the product and gain a market share. To formulate the brand activation strategy, Aubre and Liesse has to conduct an internal and external analysis. The internal analysis consists of analysis of segmentation, targeting and positioning (STP) and business model canvas. The external analysis consists of consumer behavior, porter's five forces model and competitor analysis. Based on the result analysis, the steps of a brand activation strategy are researching about the need, desire, value and behavior of the target market; determine the core message; determine the communication voice; determine the distribution channel; decide social media advertising; retargeting; and make a cooperation with the key opinion leader. The brand activation process will need to be carried out for 3 months.Keywords: Branding,Brand Activation Strategy, FashionBrand, Fashion Industry, Women’s Fashion.